Vascular Protective Effects of Morinda citrifolia Leaf Extract on Postmenopausal Rats Fed with Thermoxidized Palm Oil Diet: Evidence at Microscopic Level - C. L. G. Chong; Faizah Othman; Farida Hussan (International Journal of Vascular Medicine)
Atherosclerosis is now well understood as an inflammatory disease instead of lipid storage disorder; however, the conventional treatment is not targeted on treating the inflammation. Morinda citrifolia L. (Rubiaceae) leaf or noni leaf, which is a medicinal food (ulam) used in Traditional Malay Medicine to prevent chronic diseases, may have the potential to be formulated into a functional antiatherosclerotic agent. This study aimed to investigate the effectiveness of Morinda citrifolia leaf extract (MCLE) treatment at histological and ultrastructural level, comparing it with Simvastatin. Thirty-eight female Sprague Dawley rats were divided into five groups: Sham (Sham), ovariectomized (OVX), ovariectomized with Simvastatin 10 mg/kg (OVX+ST), ovariectomized with low dose MC 500 mg/kg (OVX+MCLD), and ovariectomized with high dose MC 1000 mg/kg (OVX+MCHD). Atherosclerosis was induced by producing oestrogen deficiency through ovariectomy and feeding with thermoxidized palm oil (TPO) diet for 12 weeks along with the treatment. The results revealed significantly (P<0.05) lower systolic blood pressure (SBP) in the group treated with MCHD compared to the untreated OVX, whereas the diastolic blood pressure (DBP) was significantly higher in the untreated OVX group compared to the Sham group. Treatment with MCHD also significantly lowered the total cholesterol (TC) level compared to the OVX. The OVX group showed significantly lower high-density lipoprotein (HDL) level compared to the Sham group. The untreated OVX group showed evident histological and ultrastructural features of vascular inflammation such as blood cells accumulation in the lumen, vacuolation of the endothelial cells, subendothelial space widening, elastic fibres disruption, increased intima media thickness (IMT), smooth muscle cells fragmentation, and perivascular adipose tissue (PVAT) deposition. All these pathological changes were less seen in the groups treated with MCLE. In conclusion, we reported the mechanism of antiatherosclerotic property of MCLE through lipids elimination and anti-inflammatory activity. In addition, we do not recommend the use of statin in the absence of dyslipidemia as it causes PVAT deposition.